2000
DOI: 10.1007/bf02237426
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in rectal cancer

Abstract: Reflecting tumor biology, apoptotic index as single variable showed no prognostic significance, whereas p53 was an independent predictor for both recurrence and survival, and bcl-2 was independently related to recurrence, but not to survival. Clinically, International Union Against Cancer stage and gender were independent prognostic factors after curative surgery for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This may provide an explanation for the more aggressive nature of CRC in young Filipinos. Indeed, as Schwandner et al [24] found in their study, p53 was an independent predictor of recurrence and survival. In addition, Gallego et al [25] noted a significantly shorter disease-free survival for their p53-positive group.…”
Section: Discussionmentioning
confidence: 53%
“…This may provide an explanation for the more aggressive nature of CRC in young Filipinos. Indeed, as Schwandner et al [24] found in their study, p53 was an independent predictor of recurrence and survival. In addition, Gallego et al [25] noted a significantly shorter disease-free survival for their p53-positive group.…”
Section: Discussionmentioning
confidence: 53%